Biodegradasi Alkil Benzena Sulfonat oleh Psedomonas cepacia - Sudiana, I Made (JURNAL BIOLOGI INDONESIA, 2002)
ABSTRACTAlkyl Benzene Sulfonate Biodegradation of Psedomonas cepacia. Alkyl Benzene Sulfonate (ABS), naturally slow biodegradable substances, and toxic to human, animal and microorganisms, is a focus of environmental studies. Microorganisms appeared to play important role on biodegradation of that substances in nature, and wastewater treatment procesess. S2 isolated from detergent contaminated soil was able to grow in media with ABS as the sole carbon source. ABS degradation took place under aerobic condition, at pH 4, temperature 30ÂºC with ?max of 0.0591-h, Ks = 3.25 mg/L, Vmax = 0.16 mg/L.hours-1, and Km = 14.52 mg/L. Analyses of 16s rDNA revealed that S2 is belonging to Pseudomonas cepacia.Key words: Alkyl Benzene Sulfononate (ABS), Pseudomonas cepacia, detergent